Fashion and Textile Ambivalences - Gianni Montagna; Maria Antonietta Sbordone (Pad, 2022)
The theme of PAD Issue 22, titled “Fashion and Textile Ambivalences”, considers the nature of the changes taking place through the sharing of testimonies, case-studies as well as theoretical and design elaborations, on emerging issues. These not only affect current and future constraints but also configure the possibility of different scenarios in the fashion and textile sectors.